Mainstreaming Women Farmers to Agricultural Extension Services in India: Perception of Extension Personnel - Uma Sah , Shantanu Kumar Dubey , S. K. Singh , Rajesh Kumar , Deepak Singh and Radha Krishna, (Indian Journal of Extension Education, 2015)
The poor access of women farmers' to agriculture extension services is an issue of concern with respect to the efficacy ofthe agriculture production situation in India. The present favorable policy environment enabling women farmers inaccessing the extension services, the extension personnel plays the crucial role of translating these policies in achievingthe desired results. In an attempt to comprehend empirically the extension personnel's perception of the issue relating tomainstreaming women farmers to agricultural extension services in India, the study was conducted among 150 ExtensionPersonnel (EP) who participated in capacity enhancement programmes during 2008-13 at ICAR- Indian Institute ofPulses Research (IIPR), Kanpur. Research variables included perception of EP on women farmers' contribution tofarming related activities, engagement of female workforce in respective district extension system, the issues related toinvolving women farmer in agricultural extension activities and the potential interventions to overcome the perceivedissue. Finding revealed that in overall pooled data more than half (56%) of EP observed that woman farmers contributed21-40 per cent to the overall agricultural activities, while 23 per cent of them perceived that women farmers contributed41-60 per cent of the total labour to agriculture activities in their respective districts. In depth activity analysis showedthat majority of the respondents reported that activities like weeding (87%), harvesting (85%), seed sowing (69%) andthreshing (48.6%) were performed by women farmers. Regarding the strength of female extension staff in their districts,about 51 per cent of the EP revealed that the percentage of women extension staff was 0 to 5 per cent of the total existingstaff strength. Majority of the EP also perceived that social taboos prevented women's involvement in the extensionactivities (61%) besides their illiteracy (39 %). Nearly half (48 %) of EPwere not satisfied with the present level of womenfarmers' access to agriculture extension services and about 83.3 per cent opined that women farmers need to be adequatelyinvolved in the agriculture extension activities. About 61 percent of them viewed that for better reach of extensionservices to women farmers, appointment of women extension staff needs priority attention. For mainstreaming womenfarmers in agricultural extension activities in India, majority of the EP suggested that designing specialized need basedtrainings for women farmers (50 %), approaching women in groups through SHGs or women's club (20 %) and reservingthirty per cent seats for women extension staff (15%) in the department may ensure better access of agricultural extensionservices to women farmers in India.